STUDENTS’ MASTERY OF PARTS OF SPEECH IN ENGLISH WRITING - Fakhruddin, Afief (Universitas Wiralodra, 2019)
The research is entitled ?students? mastery of parts of speech (noun, pronoun, and verb) in English writing. The purposes of this research are (1) to find out the students? mastery of parts of speech (noun, pronoun and verb), (2) to find out the most and least understood parts of speech among noun, pronoun and verb often found in English writing, (3) to find out the common problems faced by the  students,(4). To find out workable solutions to these problems so as to increase the students? mastery in using parts of speech (noun, pronoun and verb) in English writing. The data collections are done by giving questionnaire, test in completion item and simple English writing. The conclusion of this research are: (1) the students? mastery of parts of speech is fair (60,30), (2) the most understood parts of speech is Noun (21,66% error) and the least understood parts of speech is Verb (49,46% error), (3) common problems happened in constructing countable and uncountable noun, using possessive pronoun and pronoun  function as object, and using full verb and to be in constructing continuous and future tense. (4) The workable solutions that can be used are by using game, and quiz.